Respuesta :

we know that

The multiplicative rate of change of the exponential function between two points is equal to

[tex][f(b) / f(a) ] / (b-a)[/tex]

Let

[tex]A(1,6)\\B(2,4)[/tex]

we have that

[tex]f(a)=6\\f(b)=4\\a=1\\b=2[/tex]

substitute in the formula

[tex][4 / 6 ] / (2-1)=4/6=2/3[/tex]

Let

[tex]A(3,8/3)\\B(4,16/9)[/tex]

we have that

[tex]f(a)=8/3\\f(b)=16/9\\a=3\\b=4[/tex]

substitute in the formula

[tex][(16/9) / (8/3) ] / (4-3)=48/72=2/3[/tex]

therefore

the answer is the option

B.) 2/3



Answer:

It's B)

Explanation: